Effect of cardiac rehabilitation on heart rate recovery in patients with coronary artery disease: Effect of cardiac rehabilitation on heart rate recovery - Yilmaz, Hale; Ozbilgin, Nazmiye; Ipek , Gokturk; Bilir Kaya, Basak; Yilmaz , Mehmet; Karatas , Mehmet Baran; Bolca , Osman (Journal of Surgery and Medicine, 2024)
Background/Aim: It is well-established that individuals with coronary artery disease (CAD) often exhibit autonomic dysfunction and a reduction in vagal function is associated with increased mortality and morbidity. Vagally mediated heart rate recovery (HRR) can be assessed by analyzing the post-exercise heart rate (HR) decay. It is hypothesized that effective exercise-based cardiac rehabilitation (CR) can enhance post-exercise parasympathetic function. This study aims to evaluate the impact of CR on HRR and other cardiac parameters in CAD patients. Methods: This retrospective cohort study was conducted at a single center. It included patients with CAD who were referred to the CR unit and completed either 30 or 60 sessions. These patients were free from angina or angina-equivalent symptoms at the time of enrollment and were receiving guideline-directed medical therapy for ischemic heart disease. A customized CR program was implemented for each patient. To calculate HRR, the maximum HR during the exercise test and HR values at 1, 2, and 3 minutes after exercise cessation were recorded. The differences between the maximum HR and the HR values at the end of the 1st, 2nd, and 3rd minutes after exercise were designated as HRR1, HRR2, and HRR3, respectively. Results: This study enrolled 104 patients with CAD. Following CR, there was a significant improvement in functional capacity, as assessed by the 6-minute walk test (from 367.83 [56.58] to 381.61 [53.76], P=0.001), and endurance, as measured by the Cycle Ergometer Test Maximum Watts (from 63.22 [22.29] to 77.38 [19.87], P<0.001). CR also led to a noteworthy increase in HRR1, HRR2, and HRR3 (P=0.036, P=0.015, P=0.002, respectively). Conclusion: In our study, both the functional capacity and endurance of CAD patients improved significantly after CR sessions. Additionally, HRR showed a substantial increase following CR, suggesting that exercise-based CR can enhance post-exercise parasympathetic function. HRR may serve as a potential prognostic marker for predicting outcomes in CR.